LFSR Based Block Cipher Technique for Text - Dubey, Sakshi; Anand, Darpan; Sharma, Jayash (International Journal of Computer Sciences and Engineering, 2025)
In the world of cryptography there are a lot of techniques and their simultaneous operations, which are used for making our data transmission better, secure and fast. Today to get more and more data transmission capabilities, people tend to compromise security of their data due to non availability of better cryptography techniques to suit different needs of their data transmission. Keeping this requirement of enhanced security in mind, some new techniques are making their way in cryptography, which are reliable, fast and give better data security for transmission of different kind of data (i.e. Text, Images, Videos etc.). In this paper, authors are proposing a cryptography method for enhanced encryption and decryption with help of LFSR (linear feedback shift register), which can reliably give much desired security with more speed. In this paper the method is used only for text, it could be further modified for 2D as well as 3D images.